Analisis Numerik Pengaruh Geometri Burung Terhadap Tekanan Impak Pada Kasus Bird Strike Dengan Smoothed Particle Hydrodynamics (SPH) Model - endah yuniarti; Sahril Afandi S; Budi Aji Warsiyanto (FTK UNSURYA, 2020)
his research studies influence of bird geometry on impact pressures during bird strike, namely Hugoniot and Stagnation pressure. Bird geometry is capsule or cylinder with hemisphere end. The geometry is simulated with different L/D ratio, 1.5, 1.7, and 1.9. Elastic-plastic hydrodynamic material model is used in simulation. Bird model simulation are using smooth particle hydrodynamics method and initial velocities are 100 m/s, 200 m/s, and 300 m/s. The results show variation of L/D ratio provide Hugoniot pressure 14-25 times higher than stagnation pressure in L/D = 1.5, 12-25 times in L/D = 1.7, and 11-34 times in L/D = 1.9. Hugoniot pressures show an increased value from L/D 1.5 to 1.9 at a velocity of 100 m/s. However, for Hugoniot pressure at a velocity 200 m/s shows a value that decreases from L/D 1.5 to 1.9. The stagnation pressure ratio of L/D is lower than L/D 1.5 and 1.7 at impact velocity 100 and 200 m/s.